Studi Ornamen pada Masjid di Daerah Kelurahan Bukit Lama Palembang - Husien, Adnan; Mafra, Ramadisu (Universitas Muhammadiyah Palembang, 2024)
In general, a mosque is a spiritual place for Muslims where a deep connection between human and Allah SWT is established. Upon entering the interior of the mosque, one often encounters ornaments that contribute to the beauty and aesthetic value of the mosque. However, it is not uncommon to find mosques that adopt minimalist and simple concepts to prioritize the primary function of the mosque itself. With the presence of these ornaments in the mosque, this research aims to inventory the ornaments found in 20 mosques in the Bukit Lama district, Palembang. The research methodology employed a qualitative descriptive approach, utilizing both primary data (author's documents) and secondary data (images from Google Maps). The research findings reveal six commonly found ornaments in the 20 mosques, namely, the ? (Allah) inscription at 80%, the ? (Muhammad) inscription at 70%, Asmaul Husna ornaments at 20%, geometric patterns (mihrab) at 40%, minimalist patterns (mihrab) at 60%, and surah decorations on walls and similar areas reaching 60%.